1999
DOI: 10.7326/0003-4819-131-4-199908170-00005
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Identified Needs for Hormone Replacement Therapy Counseling: A Qualitative Study

Abstract: Many women in a managed care organization who accepted a prescription for HRT identified counseling needs that are not included in widely used HRT guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Some interviewees felt the WHI empowered them, whereas others felt they lacked the tools to assist their patients. These findings are consistent with prior studies that found that women 25 and physicians 26,27 were dissatisfied with shared decision making and had counseling needs that published guidelines did not address. In either case, in the face of uncertainty and inadequate information, interviewees felt the final choice regarding HT use comes down to a woman's preference.…”
Section: Discussionsupporting
confidence: 90%
“…Some interviewees felt the WHI empowered them, whereas others felt they lacked the tools to assist their patients. These findings are consistent with prior studies that found that women 25 and physicians 26,27 were dissatisfied with shared decision making and had counseling needs that published guidelines did not address. In either case, in the face of uncertainty and inadequate information, interviewees felt the final choice regarding HT use comes down to a woman's preference.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Long-term continuation is especially important for preventing the loss of bone mineral density (BMD), 1 a factor cited by a large percentage of patients as influencing their decision making regarding HRT. 3 A small number of low-dose estrogen formulations have been approved in the United States for preventing menopausal symptoms or osteoporosis: oral conjugated equine estrogens (CEEs) or esterified estrogens at 0.3 mg/d; oral micronized estradiol at 0.5 mg/d; and transdermal 17␤-estradiol at 0.025 mg/d. Genant et al 4 demonstrated that esterified estrogens at 0.3 mg/d for 24 months, combined with a calcium supplement, increased BMD compared with baseline and placebo.…”
Section: T He Use Of Lower Doses Of Es-mentioning
confidence: 99%
“…The need for personal consultation has been documented in previous studies 27,33 and may be a reflection of the frustrations women experienced with information searches and the decision-making process. Rather than wading through a vast amount of information sources with questionable reliability, they prefer expert advice with an opportunity to ask questions.…”
Section: Discussionmentioning
confidence: 92%